A Novel Intrusion Detection Techniques of the Computer Networks Using Machine Learning - Nilamadhab Mishra, Sarojananda Mishra (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Network intrusion is an unauthorized work of a computer network. Protecting the computer network against unauthorized users, even internal ones, is the goal of the network access programme. We will create a local network detection, which is a prophecy mold to discriminate amid "good quality" or typical associations and "appalling" associations, which sometimes referenced to as intruders or attacks. Evaluation of the findings for accessibility was the goal. In the Knowledge discovery Cups 1999 dataset for predicting, we also concentrated on machine learning-based classification to facilitate acquire greatest training and testing, to access our strategy for using currently available technologies. To generate various classification models, used varieties machine-learning based techniques and comparing each other for detecting best fit model for the computer networks with respect to time and accuracy.